2001
DOI: 10.1161/01.str.32.4.830
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque and Intima-Media Thickness Assessed by B-Mode Ultrasonography in Subjects Ranging From Young Adults to Centenarians

Abstract: Background and Purpose-To investigate relationships among plaque formation, increasing intima-media thickness, and age, we examined ultrasonographically carotid arteries of subjects who had no major atherosclerotic risk factors and who ranged in age from young adults to centenarians. Methods-We studied 319 healthy subjects (154 men, 165 women; age range, 21 to 105 years) with no history of hypertension, diabetes mellitus, or atherosclerotic disease. Mean intima-media wall thickness (IMT) of common carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
145
4
16

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(186 citation statements)
references
References 32 publications
21
145
4
16
Order By: Relevance
“…Common carotid artery IMT has also been shown to increase in a linear manner throughout life (20). And other studies have reported that carotid arterial IMT was greater in hypertensive than in normotensive subjects who were matched for age and cardiovascular risk factors (16,21).…”
Section: Discussionmentioning
confidence: 97%
“…Common carotid artery IMT has also been shown to increase in a linear manner throughout life (20). And other studies have reported that carotid arterial IMT was greater in hypertensive than in normotensive subjects who were matched for age and cardiovascular risk factors (16,21).…”
Section: Discussionmentioning
confidence: 97%
“…The systemic vascular lesion caused by hypertension may influence the rate of GFR decline after age 50 and older. A previous study reported that the mean common carotid intima-media thickness (IMT) increased in a linear manner with age in healthy subject, and the increase was more significant in the subjects with age 50 and older than in subjects with younger age (19). The carotid IMT was greater in patients with CKD than healthy controls at age 50 and older; however, the IMT in the patients was not different from that of healthy controls at age 40-49 (20).…”
Section: Fig 3 A: Effects Of Proteinuria On the Rate Of Decline In mentioning
confidence: 93%
“…In other words, excessive intimalmedial thickening in humans is not necessarily synonymous with "early" or "subclinical" atherosclerosis. 45 Rather, as the arterial wall becomes remodeled during aging, it becomes super-sensitive to risk factors (eg, high-lipid diets, etc) not usually encountered by animals. The interaction of these risk factors with the age-altered vascular substrate is clearly exemplified by the reduced threshold for or accelerated development of experimental atherosclerosis in older animals subjected to an atherogenic diet.…”
Section: Links Between Arterial Aging and Atherosclerosismentioning
confidence: 99%